PECULIARITIES OF ELABORATING AND MAKING COMPLEX MARKETING DECISIONS IN UNSTEADY MANAGEMENT SYSTEMS - S. Karpova (Управленческие науки, 2015)
The experience of Russian companies which passed crises of 2008-2009 and 2014-2015, demonstrated the impossibility of using the standard approach for decision-making process under conditions of increased instability. The article deals with the specifics of managerial decision-making process in a crisis that takes into account additional restrictions imposed by the new conditions in the market. Peculiarities of marketing decision-making in the organization during crisis caused by various factors have been quoted. The basic techniques for solution development within the ordinary management and in conditions of instability are analyzed. The article includes approaches to the development of the algorithm of management decisions in the field of marketing and directions of their adaptations for management purposes in conditions of instability. The methodic is characterized not only by crisis management in the sequence of stages of development management decisions, but also by the use of certain methods of analysis and evaluation, organization of work, choose of alternatives, etc. The paper describes the differences in integrated marketing solutions depending on the stage of instability in the organization. Criteria for decision-making in terms of crisis management also have specific features: in the framework of stability these criteria is to achieve the strategic aims of the organization and increasing the value of companion a long term basis and maximize profits in the short term period. Managing unstable economic system implies optimizing costs, including reducing some non-core units and business processes. Losses in the value of assets or income are inevitable, so it is necessary to build a system of implementing successive decisions which at any given time will lead the development of the organization to a new level. It is noted that in the framework of the instability the need for professional hysteresis management increases. In marketing this phenomenon is known as a temporary change in one factor or process which leads to long-term changes in other factors.